2014
DOI: 10.1186/2193-8997-3-10
|View full text |Cite
|
Sign up to set email alerts
|

Percent plans, automatic admissions, and college outcomes

Abstract: Access to selective universities is highly coveted because of the perception that attending one provides opportunities otherwise difficult to obtain. To broaden access to the state's flagship universities in a manner that does not rely on conventional affirmative action, Texas passed the Top Ten Percent Plan in 1997, which guarantees automatic admission to any public university in the state to students in the top decile of their high school class. We estimate the effect of eligibility for automatic admissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
2
16
0
Order By: Relevance
“…First, differences in state college quality mix, admission policies, and pricing strategies provide plausibly exogenous variation in the budget sets facing students and their parents. Niu and Tienda (2010) and Daugherty, Martorell, and McFarlin (2014) estimate large effects of guaranteed admission to in-state public colleges through the Texas Top 10% rule on college choices for eligible students. Cohodes and Goodman (2014) estimate similarly large effects of in-state-specific scholarships in Massachusetts, lowering the 20 average quality of college attended for eligible students who chose in-state colleges over more selective outside options.…”
Section: Identificationmentioning
confidence: 99%
“…First, differences in state college quality mix, admission policies, and pricing strategies provide plausibly exogenous variation in the budget sets facing students and their parents. Niu and Tienda (2010) and Daugherty, Martorell, and McFarlin (2014) estimate large effects of guaranteed admission to in-state public colleges through the Texas Top 10% rule on college choices for eligible students. Cohodes and Goodman (2014) estimate similarly large effects of in-state-specific scholarships in Massachusetts, lowering the 20 average quality of college attended for eligible students who chose in-state colleges over more selective outside options.…”
Section: Identificationmentioning
confidence: 99%
“…While statewide analyses of the effects of the percent plan have yielded negative results on the use of this admissions alternative as a replacement for affirmative action, the analysis of one district in Texas employing a regression discontinuity design found some limited influence of the percent plan on college enrollment in flagship institutions in Texas for both White and minority (defined in the study as Asian, Black, and Hispanic) students. The results are tempered by the fact, however, that the study only considered one large urban district and found the strongest impacts only for students who attended high college‐sending high schools (Daughtery, Martorell, & McFarlin, ). That is, any effect of the percent plan on flagship enrollment is concentrated in high schools that already send high percentages of students to college.…”
Section: Accessing Collegementioning
confidence: 85%
“…As noted in the previous section, non-continuities in the ELC GPA running variable at popular high school grade point averages could bias these estimates, likely upwardly-biasing the compet- 29 Students who take gap years following high school are categorized here as non-enrollees, as are the fewer than 10 percent of students who mask their non-UC student records, making them unobserved in the National Student Clearinghouse enrollment records. 30 My findings suggest that the ELC program differed sharply from the Texas Top Ten program studied by Daugherty, Martorell, and McFarlin Jr. (2014), who find that one urban school district's students pulled into Texas's flagship public universities by the state's Top Ten program tended to come from similar-quality private universities. Those authors also find suggestive evidence that Top Ten admissions had little effect at more-disadvantaged high schools; as shown below, this was not the case for California's ELC program.…”
Section: Enrollment Dynamicsmentioning
confidence: 89%